Гравітаційне мікролінзування еліптичного джерела поблизу каустики-складки - Александров, О.; Жданов, Валерій Іванович; Куйбаров, А. (Київський національний університет імені Тараса Шевченка, 2018)
Розглянуто коефіцієнт підсилення блиску протяжного джерела з гаусівським еліптичним розподілом поверхневої яскравості поблизу каустики-складки гравітаційно-лінзової системи. Для нього отримана аналітична формула, що враховує друге наближення за параметром близькості до каустики. У цьому наближенні беруть до уваги відповідні похідні лінзового потенціалу аж до п'ятого порядку. Знайдена формула містить залежність коефіцієнта підсилення від координат центра джерела, його геометричних розмірів та його орієнтації щодо каустики. На модельному прикладі проведено порівняння аналітичних розрахунків кривих підсилення для різних орієнтацій еліптичного джерела, а також для колового джерела з тією ж світністю.

We consider the amplification factor for the luminosity of an extended source near the fold caustic of the gravitational lens. It is assumed that the source has elliptical shape, and the brightness distribution along the radial directions is Gaussian. During the microlensing event the total brightness of all microimages is observed, which changes when the source moves relative to the caustic. The main contribution to the variable component is given by the so-called critical images that arise/disappear at the intersection of the caustic by the source. The amplification factor for the critical images of an extended source is given by the following formula [Formula] Here B(Z) is the brightness distribution of the source in the coordinate system associated with its center; Yc,i are the coordinates of this center in the coordinate system with origin at the caustic point; Kcr(y) is the total amplification of two critical images of the point with the coordinates y. Brightness of the elliptical source in its own coordinate system is B(z) = exp(-[(z1/a)^2 + (z2/b)^2]), where a and b are the semi-major and semi-minor axis of the reference ellipse. Earlier, by an expansion in the generalized Taylor series in the neighborhood of the point yi = 0, a formula for Kcr(yi) was obtained, which takes into account the derivatives of the lens potential up to the fifth order (Alexandrov et al // Astron. Lett., 2010). It was used to calculate the amplification of a pair of critical images of an extended circular source with various brightness profiles (Alexandrov, Zhdanov // Mon. Not. Roy. Astron. Soc., 2011). In the present paper we obtained an analogous formula for elliptical Gaussian source. The formula involves a dependence on the coordinates of the source centre, its geometric dimensions, and its orientation relative to the caustic. We show that in the linear caustic approximation the amplification of the circular and elliptical sources is described by the same (rescaled) formula. However, in the next approximations the differences are significant. We compare analytical calculations of the amplification curves for different orientations of an elliptical source and for a circular source with the same luminosity for the model example.
Gravitational microlensing of an elliptical source near a fold caustic
Keywords: гравітаційні лінзи; каустика-складка; мікролінзування; еліптичне джерело; коефіцієнт підсилення; аналітичні формули; gravitational lenses; fold caustic; microlensing; elliptical source; amplification factor; analytical formulas